Context-Aware Mobile Applications: Taxonomy of factors for building approaches - Gómez Torres, Estevan R. (2018)
Fusion of sensing mechanisms inside mobile devices (e.g.: GPS, accelerometers) have driven the growth of context-aware mobile applications. Currently, there are building approaches for this kind of applications, but these do not have the flexibility, for example, to derive applications combining different location sensing mechanisms. In this paper, we present a first proposal of a taxonomy of factors that could be considered by context-aware mobile application building approaches, in order to provide variability in the kinds of derived applications. The aim is to generate a discussion that can contribute to the unification of aspects that should be addressed by these building approaches. To complement the taxonomy, we present the analysis of an interview that was conducted with regard to developers who use (or could use) these building approaches. We hope this will enrich the discussion in relation to this kind of approaches.